ПОРІВНЯННЯ ІМПЕДАНСНИХ ЛАНОК ДЛЯ ПЕРЕТВОРЮВАЧІВ З ДЖЕРЕЛОМ НАПРУГИ - Гусев, О.О.; Чуб, А.І.; Вінніков, Д.В. (Інститут електродинаміки НАН України, Київ, 2015)
Impedance networks cover the entire realm of electric power conversion in a wide range of applications. Many converter topologies are presented in the literature in order to overcome the limitations of the traditional voltage source, current source, classical buck-boost, unidirectional and bidirectional converter topologies. This paper presents review of the main exist impedance-source networks for voltage-fed converter applications. The detailed analysis of their pros and cons is revealed. Boost factor of the different impedance networks is compared. The impedance networks that are based on the coupled inductors can have higher boost performance due to the adjustable turn’s ratio of the windings. The comparison in terms of input current behavior is presented as well. Modification examples of the impedancesourced converters are separately considered. Design principles of the isolated and cascaded converters based on the impedance-source networks are shown. The field of application is discussed. Doe to the wide voltage regulation range along with cross conduction immunity discussed solutions are promising for the renewable energy applications. References 18, table 1, fіgures 5.